(untitled) (Ozone Therapy Global Journal, 2011)
The sensibilities for the sick people and looking for the best available and less expensive means to cure them, has been one constant features of the Italian Professor Velio Bocci, to the point that most of his entire life has been devoted to helping those in need of scientific medical assistance. In a similar way as his Siena ancestor countryman Giacomo Sansedoni did. A picture of this prominent physician is at the walls of the Siena Santa Maria della Scala Museum painted by the Siena Baroque painter Bernardino Mei (XVII Century) This physician of the XVII Century Giacomo Sansedoni decided to donate all his library and important wealth to the Siena Santa Maria della Scala which was one of “the first hospitals in Europe, with its own organization set up to care for pilgrims, assist the poor and provide for abandoned children.” (1000 years of life). http://www.santamariadellascala.com/w2d3/v3/view/sms2/storia–22/index_en.html